Red cell distribution width may help to discriminate synthetic cannabinoid users in the emergency department - Kalafat, Utku Murat; Dogan, Serkan (International Journal of Research in Medical Sciences, 2019)
Background: Differentiating bonsai users from the suspected users is problematic. The aim was to determine whether bonsai using men and the others can be distinguished via the hemogram parameters such as mean corpuscular volume (MCV), mean platelet volume (MPV), red cell distribution width (RDW) and Plateletcrit (PCT). Methods: In this retrospective case-control study, a total of 138 men admitted to ED were investigated in Kanuni Sultan Suleyman Hospital, Istanbul, Turkey in 2014. The patients were divided into 2 groups which were the first group had included bonsai users whereas the second group was consist of men not using bonsai. Complete blood count tests were performed on all patients. Results: Among the suspected bonsai users, 68 were diagnosed to use bonsai. It was found that MCV, RDW and PCT levels were significantly higher in bonsai users compared to controls while MPV levels were lower in the users. Author put all these parameters to logistic regression analysis model using enter method. RDW (OR: 3.98, 95%CI:2.180-7.266, p<0.0001), MPV (OR:0.526, 95%CI:0.373-0.742, p<0.0001) and PCT (OR:<0.0001, 95%CI:0.000-0.058, p=0.007) were independent variables to discriminate bonsai users from that of suspected users. The most promising parameter to differentiate bonsai users from suspected users was RDW (AUC: 0.748, 95%CI: 0.668-0.828, p:<0.0001). The optimal cut-off value was found as 10.8 for RDW with a sensitivity, specificity, +LR and -LR as 66.2%, 64.3%, 1.85, 0.53, respectively. Conclusions: RDW marker can be a reliable parameter to discriminate bonsai users from that of suspected users with moderate sensitivity and specificity.